Rate Monotonic with Minimum Release Time First for Scheduling Periodic Tasks in Embedded System - Chitranshi, G; Gaur, M; Gupta, D (Confluence 2013 : the Next Generation Information Technology Summit : 4th International Conference, Mega trends of IT- Social, Mobile, Analytics, Cloud : 26-27, September, 2013, Amity University Campus, Sec-125, Noida (New Delhi NCR), India, 2013)
Rate Monotonic algorithm is used for scheduling tasks in real time systems. This paper presents an approach to modify the Rate Monotonic algorithm and develop a new algorithm to schedule fixed priority tasks in real time systems. The comparison between the fixed priority algorithms and RM-MRT (Rate Monotonic with Minimum Release Time) has been done to find out it's utility in real time environment.